Odpowiedź :
Odpowiedź:
[tex](7 - 5\frac{2}{5} )*\frac{1}{4} = (\frac{7}{1} - \frac{27}{5} )*\frac{1}{4}=(\frac{35}{5} - \frac{27}{5})*\frac{1}{4}=\frac{8}{5} * \frac{1}{4}=\frac{2}{5} \\ \\[/tex][tex](\frac{7}{9} -\frac{47}{72} ):1\frac{1}{4} = (\frac{56}{72}- \frac{47}{72}):\frac{5}{4} =\frac{1}{8} *\frac{4}{5} =\frac{1}{10}[/tex][tex]6*(1\frac{1}{3} )^{2} = 6*(\frac{4}{3})^2=6*\frac{4}{3} *\frac{4}{3} =6*\frac{16}{9} =2*\frac{16}{3} =\frac{32}{3}[/tex][tex](\frac{5}{7} )^2:\frac{5}{7} =\frac{5}{7} *\frac{5}{7}:\frac{5}{7} =\frac{25}{49}: \frac{5}{7}-=\frac{25}{49}:\frac{7}{5} =\frac{5}{7}\\[/tex]
[tex](\frac{2}{5} )^2+4\frac{1}{2} *2\frac{2}{3} = \frac{2}{5} *\frac{2}{5} +\frac{9}{2} *\frac{8}{3} =\frac{4}{25}+\frac{12}{1} = \frac{4}{25}+ \frac{300}{25} =\frac{304}{25} =12\frac{4}{25}[/tex][tex](\frac{1}{3} - \frac{1}{4} )^2=(\frac{4}{12}- \frac{3}{12})^2=(\frac{1}{12} )^2=\frac{1}{144}[/tex]
Szczegółowe wyjaśnienie: